Intelligent vs. Cultural: Research on the path to improve the resilience of urban and rural community governance based on the AHP-FCE model - Hongxun Xiang; Yang Yang; Xingyu Qi (Heliyon)
Community resilience is a core component of grassroots governance modernization, and community resilience shows different characteristics depending on the type of community. Existing research on community resilience mainly uses direct questionnaire data, relatively ignoring the differences in weights of various dimensions. Different categories of community resilience components play different roles in community resilience. Based on this, the study cited the logic of the AHP-FCE model and added objective data based on empowering resilience, thus making up for the model's shortcomings while giving full play to the model's advantages. The quantitative analysis of 353 questionnaires from five urban districts and five rural communities in the sample city was based on the community resilience evaluation model. In the current process of community resilience construction, there are typical problems of a lack of cultural resilience in urban community resilience construction and a need for more intelligent resilience in rural community resilience construction. The key to future community resilience construction is reconciling the relationship between cultural and intellectual resilience to solve the problem of targeting deviation in urban communities and rural community resilience construction. It is necessary to adhere to the spirit of “long-term construction” to build the cultural resilience of urban communities, implement the path of “digital empowerment” to make the intelligent resilience of rural communities, and adhere to the standard of “complete redundancy” to form an urban and rural community resilience governance mechanism gradually, and then Move towards more resilient urban and rural community governance and help realize the modernization of grassroots governance.